TOURISM STATISTICS IN GEORGIA (International Journal of Innovative Technologies in Economy, 2018)
By the beginning of the 21st century, tourism has been formed as a sustainable development branch of economics, which has established special place in global economic structure. Tourism makes significant impact on the incentive of economic growth, on creating employment places and shaping positive environment, which is positively reflected on other economic activities. The role of statistics is important in the management of economy. That is why the quantitative study of the processes and events in tourism is of high importance. Right with the help of statistic methods is the information about public lifestyle structure elements – labor and labor hours gained, processed and analyzed. Statistics can study the level, potential of tourism development by general and private methods. It can gain public services and other information. Statistics can find out unfriendly factors for tourism development, define tourism influence on the economic growth of the country and can work out recommendations for infrastructure optimization on the basis of its analysis.